Nutritional impact study of the income generation for vulnerable group development program: report of July 1995 - Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
BRAC through its collaborative effort with the Government of Bangladesh has been implementing the Income Generation for Vulnerable Group Development Programme (IGVGDP) with the aim of improving the destitute rural women's 1 i fe through involving them into income generating and other development activities. The participating women receive 31.25 kg wheat per month as food aid for a set period of two years along with other development inputs from BRAC and the GOB. Nutrition and other health messages are imparted in the regularly held issue based meetings and through home visits by the para-professionals and programme field staff. Nutritional status indicators have been considered as a proxy of overall development of the programme participating households. The aim of this study is to see if the programme after about a year of postimplementation has made any impact on the nutritional status of the pre-school children. This study is based on data collected in July 1995 on 202 Households participated In the IGVGD programme from Tanga i 1 Sadar than a, 17 2 non-programme con t ro 1 househo Ids from within the programme area and 164 non-programme control households from outside the programme area (Kalihati thana). The study children's anthropometric and household's socioeconomic data were collected by the RED interviewers through home visits using structured pre-tested questionnaire. The data suggest positive changes for some selected socioeconomic indicators of the households participated in the IGVGD programme compared to the control households. Sanitary and hygiene practice were also found to be better among the IGVGD households. A decreased trend was found in the proportion of severely malnourished children (according to Gomez classification) in the programme househo Ids. Wasting as defined by reduced weight for height was significantly lower in the IGVGD households ( 7. 8%) ' compared to the non-programme households from within (12.1%) and outside (18.9%) the programme area. The proportion of the underweight children was also lower in the programme children (63.8%) than both the non-programme children (69.6% and 78.1% respectively). Examining the results of this study it may be concluded that the IGVGD programme in addition to socioeconomic upl i ftment of the rural destitute women is able to improve nutritional status of the vulnerable groups such as the pre-school children.